Enhanced energy harvesting from rooftop PV array using Block Swap algorithm - Kour, Jasdeep; Shukla, Anup (Energy conversion and management, 2021)
•Low-cost effective shade dispersion and power enhancement technique for SPV array.•Proposed reconfiguration technique is applicable to square (m × m) or non -square (m × n) dimensioned rooftop SPV array.•Least length of dc cables without any additional circuitry to achieve objective.•One-time PV array reconfiguration at the time of rooftop SPV array installation.•Simulation tested for various present observable and prospective shading patterns. Partial Shading conditions arising from tall buildings, upcoming infrastructural setup, trees, passing clouds, and other factors adversely affect the Photo-Voltaic (PV) array output power and overall efficiency. This paper proposes a field implementable PV array reconfiguration technique named Block Swap-inspired Fixed Column (BSFC) reconfiguration. The proposed reconfiguration technique makes one-time connections (at the time of PV array installation). It eliminates the need to physically relocate the PV panel as is propounded by various static and dynamic reconfiguration techniques reported in the literature. The physical relocation of PV panels is not a viable real-time solution for shade dispersion due to the shading patterns' stochastic nature. The proposed technique works well for both square (m × m) and non-square matrix (m × n) dimensions of the PV array and provides better results for all shading patterns witnessed over the length of the day. The effectiveness and feasibility of the proposed reconfiguration technique (BSFC) are tested on a solar PV rooftop array installed at IIT Jammu Campus, and the simulation is done on the MATLAB platform. Simulation results confirm the potential and effectiveness of BSFC after comparison with other reconfiguration methods like Series-Parallel (SP), Total Cross Tied (TCT), Odd-Even (OE), Odd-Even Prime (OEP). The proposed technique provides enhanced power output while utilizing the least length of the connecting dc cables and the least electrical displacement w.r.t initial electrical connections. BSFC technique applies to any string length of the PV array without additional support circuitry and results in lower voltage drops across the length of the dc cable.